Correlation Matrix of Groundwater Quality Parameters along the Red Sea Coast (University of Khartoum Engineering Journal, 2022)
Groundwater samples, collected from different locations along coastal zone in the Red Sea State (RSS), Sudan, were analyzed for their physicochemical characteristics. Twenty six samples from borehole locations of groundwater were investigated. The investigation focused on the determination of physicochemical parameters such as electrical conductivity (EC), pH, total dissolved solids (TDS), chloride, sulphate, fluoride, sodium, calcium and some other parameters. Groundwater suitability for domestic and irrigation purposes was examined in comparison with World Health Organization(WHO) guidelines for drinking water quality and Indian Drinking Water Standards (BIS), which indicate that the groundwater in most areas, are not suitable for domestic and agriculture purposes. Statistical properties of the physiochemical parameters were computed. The correlation coefficients between the different water quality parameters were computed and organized in a matrix form. TDS and EC are perfectly correlated to chloride, CaCO3 and sodium and significantly correlated to fluoride, calcium and magnesium. Thus, the major exchangeable ions were found to be correlated positively indicating the origin of major cations to be dissolution/precipitation processes.